Qualitative modeling of spatial orientation processes using a logical network of necessary and sufficient conditions - Riecke, B. E.; Heyde, M. von der (Object Perception and Memory (OPAM), 2003)
INTRODUCTION: Findings from spatial orientation and navigation experiments are typically rather diverse and highly task-dependent. In this paper, we attempted to model the underlying spatial orientation processes by analyzing their logical and functional relations. This eventually led to a network of necessary prerequisites and sufficient conditions for spatial orientation, spatial presence, and spatial updating. LOGICAL MODELING: How does logical modeling work? For example, it is evident that ego-motion perception cannot occur without some kind of motion perception. That is, intact ego-motion perception seems to logically depend on intact motion perception (NO motion perception NO ego-motion perception). Conversely, if we observe intact ego-motion perception, we can conclude that motion perception must also be intact, which can be represented as ego-motion perception motion perception (as $\neg$B =⇒ $\neg$A ≤⇒ A =⇒ B). OVERVIEW OF THE MODEL: Spatial behavior and spatial perception are the main components of the perception-action cycle and constitute the top and bottom part of the framework, respectively (see Figure 1). Meaningful spatial behavior is essentially based and logically dependent on spatial perception, and is mediated by several possible spatial orientation processes. At the bottom part of the framework, we distinguish mainly between two branches, a relative motion branch on the left side and an absolute location branch on the right side (see Figure 1). The left "relative motion branch" is based on path integration of perceived motions. It is responsible for generating the perception of ego-motion (e.g., vection) and the continuous updating of the self-location in space. The right "absolute location branch" constitutes an alternative approach to finding ones way around, by using landmarks as reference points. Object/landmark memory is hereby involved in the recognition of salient features in the environment. In addition to the left and right branch, we propose a third pathway that is responsible for robust and automated spatial orientation. That is, if we want to know where we are without having to think much about it, we need some process that allows for quick & intuitive spatial orientation and prevents us from getting lost, even when we do not constantly pay attention. To achieve this, some automated process (called "automatic spatial updating" or just "spatial updating") needs to always update our egocentric mental reference frame of the surround during ego-motions, such that it stays in close alignment with the physical surround. We distinguished between four qualitatively different aspects or properties of spatial orientation processes: adaptable, quick & intuitive, accurate & precise and abstract strategies. These different aspects of spatial behavior seem to depend logically on different underlying spatial orientation processes and data structures. We categorized those processes into cognition (abstract mental reasoning), piloting (landmark-based navigation), continuous spatial updating and instantaneous spatial updating. The complete framework is presented in Figure 2 for reference. Instead of trying to explain the whole framework, we would instead like to focus here on the two spatial updating processes that are responsible for robust and effortless spatial orientation. CONTINUOUS VS. INSTANTANEOUS SPATIAL UPDATING: "Continuous spatial updating" refers to the largely automated and reflex-like process of updating our mental egocentric reference frame during self-motions based on continuous motion cues. Continuous spatial updating is based on the integration of the perceived ego-motion, whereas instantaneous spatial updating is based on object and scene recognition (see Figure 2). Instantaneous spatial updating occurs for example in the moment of waking up after having fallen asleep on a bus: As soon as we look out of the window and recognize the outside scene, we are automatically re-anchored to that reference frame. That is, we immediately know where we are without any conscious effort and without being able to suppress that re-anchoring (instantaneous spatial updating) of our egocentric reference frame. Embedding these two spatial updating processes into a framework of logical connections allows to clearly disambiguate between them: Either of these processes may enable (i.e., is a logical prerequisite for) quick & intuitive spatial orientation (see Figure 2). Only instantaneous spatial updating, however, allows for accurate & precise spatial orientation, as it is based on the localization and identification of landmarks embedded into a consistent scene. This has specific implications that can be experimentally tested and controlled. As a first test of the model, we performed a series of spatial updating experiments in different virtual environments. For example, we selectively disabled either the relative motion branch or absolute location branch by either removing all useful landmarks or by eliminating all motion cues in a "teleport" condition, respectively. In the latter teleport experiment, instantaneous spatial updating was able to compensate for the missing motion information and resulting lack of continuous spatial updating without any significant decrease in performance (Riecke, von der Heyde, & Bülthoff, 2002). This confirmed our distinction between continuous and instantaneous spatial updating as two separate processes that can serve as a mutual backup-system. CONCLUSIONS: This framework is intended as a working hypotheses that can assist in analyzing spatial situations and experimental results. It provides a coherent representation for the large number of experimental paradigms and results and can thus allow for a unifying big picture that might help to structure and clarify our reasoning and discussions. In particular, it proved helpful in understanding the implications if certain processes related to spatial orientation are impaired or defunct (see, e.g., Riecke, 2003, part IV). Furthermore, the human factors issues involved in all Virtual Reality applications can be tackled by analyzing the relevant simulation and display parameters necessary for quick and effortless spatial orientation: Most importantly, any application that does not enable automatic spatial updating should decrease quick and effortless spatial orientation performance and hence unnecessarily increase cognitive load. Only future research, however, will enable us to rigorously test the proposed logical framework and refine or extend it where appropriate. SUPPORT: Max Planck Society, European Community (IST-2001-39223, FET Proactive Initiative, project "POEMS" (Perceptually Oriented Ego-Motion Simulation, www.poems-project.info), and Deutsche Forschungsgemeinschaft (SFB 550, B2). REFERENCES: Riecke, B. E. (2003). How far can we get with just visual information? Path integration and spatial updating studies in Virtual Reality. Ph.D. thesis, Eberhard-Karls-Universität Tübingen, Fakultät für Physik. Available: www.kyb.mpg.de/publication.html?publ=2088. Riecke, B. E., von der Heyde, M., & Bülthoff, H. H. (2002). Teleporting works - Spatial updating experiments in Virtual Tübingen. In OPAM, Talk presented at the 10th annual meeting of OPAM, Kansas City, United States. Available: www.kyb.mpg.de/publication.html?publ=1952.
Keywords: Riecke; Riecke_2003; bernhard-riecke; iSpaceWeb; markus-von-der-heyde; spatial updating; talkWithoutPaper